Cracking the Skin Barrier: Liquid-Liquid Phase Separation Shines under the Skin - Alexa Regina Chua Avecilla; Felipe Garcia Quiroz (Elsevier, 2021)
Central to forming and sustaining the skin's barrier, epidermal keratinocytes (KCs) fluxing to the skin surface undergo a rapid and enigmatic transformation into flat, enucleated squames. At the crux of this transformation are intracellular keratohyalin granules (KGs) that suddenly disappear as terminally differentiating KCs transition to the cornified skin surface. Defects in KGs have long been linked to skin barrier disorders. Through the biophysical lens of liquid-liquid phase separation (LLPS), these enigmatic KGs recently emerged as liquid-like membraneless organelles whose assembly and subsequent pH-triggered disassembly drive squame formation. To stimulate future efforts toward cracking the complex process of skin barrier formation, in this review, we integrate the key concepts and foundational work spanning the fields of LLPS and epidermal biology. We review the current progress in the skin and discuss implications in the broader context of membraneless organelles across stratifying epithelia. The discovery of environmentally sensitive LLPS dynamics in the skin points to new avenues for dissecting the skin barrier and for addressing skin barrier disorders. We argue that skin and its appendages offer outstanding models to uncover LLPS-driven mechanisms in tissue biology.